2022
DOI: 10.1038/s41598-021-04021-0
|View full text |Cite
|
Sign up to set email alerts
|

Research on the rapid combustion process of butane under microwave discharge

Abstract: To study the combustion process of fuel in the microwave plasma torch, we designed a butane microwave plasma device exploiting a tungsten rod as an electrode. Through analysis of the image record by high-speed camera, we found that the discharge of butane microwave plasma torch is a cyclic process at atmospheric pressure at a frequency  of around 100 Hz. During the discharge, the active particles continuously diffuse from the electrode to the outside like the bloom of the flower. Then, the variation of plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Fig. 16 Diagram of the effect of changing the injector angle on fuel mass In Fig. 16, the most suitable injector angle is 40 to 45 degrees, creating the minor fuel film on the walls.…”
Section: Table 1 Different Injector Anglementioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 16 Diagram of the effect of changing the injector angle on fuel mass In Fig. 16, the most suitable injector angle is 40 to 45 degrees, creating the minor fuel film on the walls.…”
Section: Table 1 Different Injector Anglementioning
confidence: 99%
“…According to this study, a multiphase flow liquid injection system can generate cavitating flows, validating the multiphase CFD simulation. Tang et al [16] found that the release of the butane microwave plasma torch is a cyclic process at atmospheric pressure and a frequency of around 100 Hz. According to this research, during the discharge, the active particles continuously diffuse from the electrode to the outside.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous methods for efficient plasma ignition, electromagnetic energy stands out for its exceptional proficiency. , This approach concentrates electromagnetic waves intensely to trigger conditions conducive to plasma breakdown. Various components, including surfatrons, slot antennas, and resonant cavities, are employed in these systems, culminating in the development of resonator-based plasma sources (RPSs). , RPS systems bring unique advantages, such as the absence of electrodes, effectively preventing contamination, and remarkable energy efficiency across a wide range of gas pressures .…”
Section: Introductionmentioning
confidence: 99%